التقديم والتأخير في ديوان الشعر العربي لأدونيس -نماذج مختارة- - ISMAEL , HASAN MOHAMAD SAAEED; HUSSEIN, DILKHOSH JARALLAH (Journal of Duhok University, 2023)
The research tagged with (Presentation and Delay in Adonis's Divan of Arabic Poetry) deals with the phenomenon of introduction and delay in Adonis's Divan of Arabic Poetry by monitoring the positions of submission and delay in the Diwan and selecting models for analysis and study in order to reveal the stylistic shift caused by introduction and delay in the synthetic and semantic levels of the poetic language.The research plan is based on an introduction, three sections, and a conclusion. As for the introduction, we clarified through it the concept of submission and delay, and the students’ interest in it, past and present, as a stylistic shift on the synthetic level. Presenting the predicate to the subject, and the second section was titled (Presenting the Object with It), in which we dealt with the poetic models in which it was evident that the object was prioritized over the verb and the subject. And the neighbor and the accusative, and the conclusion included finally the most important findings of the research.The research relied on a variety of sources, including ancient and modern ones, and perhaps the most prominent sources that were employed: Adonis’s (Divan of Arabic Poetry) as the main sample for the applied side of the research, as well as the book (Evidence of Miracles) by Abdul Qaher Al-Jurjani, and the book (Arabic Rhetoric - Another Reading) Dr. Mohamed Abdel-Muttalib for the theoretical side of the research.The research aims to prove that introduction and delay are phenomena that cause a shift in the poetic language at the structural and semantic levels, while the importance of the research comes from the collection chosen for the study as a poetic anthology that included Arabic poetry from the pre-Islamic era to the beginning of the twentieth century.